2014
DOI: 10.1080/09168451.2014.877816
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Saccharomyces cerevisiae to improve succinic acid production based on metabolic profiling

Abstract: We performed metabolic engineering on the budding yeast Saccharomyces cerevisiae for enhanced production of succinic acid. Aerobic succinic acid production in S. cerevisiae was achieved by disrupting the SDH1 and SDH2 genes, which encode the catalytic subunits of succinic acid dehydrogenase. Increased succinic acid production was achieved by eliminating the ethanol biosynthesis pathways. Metabolic profiling analysis revealed that succinic acid accumulated intracellularly following disruption of the SDH1 and SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…The expression of the mae1 gene was critical in both strain backgrounds and led to an almost three times higher succinate titer in the wildtype (REF‐6) and a twofold increase in the TAM strain (TAM‐6) compared with the strains carrying the succinate synthesis pathway but lacking the transporter. In several other studies, introduction of a heterologous transporter function has been shown to be critical for the extracellular accumulation of several organic acids including succinate …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the mae1 gene was critical in both strain backgrounds and led to an almost three times higher succinate titer in the wildtype (REF‐6) and a twofold increase in the TAM strain (TAM‐6) compared with the strains carrying the succinate synthesis pathway but lacking the transporter. In several other studies, introduction of a heterologous transporter function has been shown to be critical for the extracellular accumulation of several organic acids including succinate …”
Section: Resultsmentioning
confidence: 99%
“…The expression of the mae1 gene was critical in both strain backgrounds and led to an almost three times higher succinate titer in the wildtype (REF-6) and a twofold increase in the TAM strain (TAM-6) compared with the strains carrying the succinate synthesis pathway but lacking the transporter. In several other studies, introduction of a heterologous transporter function has been shown to be critical for the extracellular accumulation of several organic acids including succinate [5,18,36] The TAM strain did not produce ethanol, the main byproduct formed by the wild-type strain in concentrations as F I G U R E 2 Comparison of the reference and TAM strains engineered for succinate production. The strains were cultivated in mineral salt medium with 5% glucose as substrate and supplemented with 22 mM formate under microaerobic conditions (shaking frequency 90 rpm).…”
Section: Chromosomal Expression Of the Heterologous Pathways In The Wmentioning
confidence: 96%
“…However, several important issues in metabolic engineering need to be solved for the efficient production of succinic acid, such as high alcoholic concentration during the fermentation process. To reduce ethanol production, multiple genes encoding alcohol dehydrogenase (encoded by adh ) and pyruvate decarboxylase (encoded by pdc ) were deleted . The modified strain with the deletion of pdc1 , pdc5 , pdc6 , his3 , fum1 , and gpd1 , and the introduction of a reductive pathway led to an improved succinic acid production of 13.0 g L −1 with a yield of 0.13 g g −1 at pH 3.8 through regulation of biotin and urea levels .…”
Section: Succinic Acid Production By Metabolically Engineered Strainsmentioning
confidence: 99%
“…Finally, overexpression of isocitrate lyase, Icl1p, in the evolved strain, resulted Deletion of PDC1 and expression of multiple copies of L-LDH from bovine [30] Inhibition of L-LDH consumption by deletion of DLD1 and JEN1, elimination of ethanol and glycerol production by deleting PDC1, ADH1, GPD1 and GPD2, and improvement of lactic acid tolerance by adaptive evolution and overexpression of HAA1 [31] Overexpression of HXT1 and HXT7 hexose transporters [32] Repression of ethanol production by deleting PDC1 and ADH1 and enhanced acetylCoA supply by the introduction of the genes encoding acetylating acetaldehyde dehydrogenase enzyme from Escherichia coli [33] Enhancement of lactic acid transport by expressing JEN1 and ADY1 [34] Expression of ESBP6, a novel target isolated by screening a multi-copy yeast genomic DNA library [35] in a succinic acid yield of 0.07 mol/mol glucose under aerobic conditions without glycine addition. Metabolic proiling analysis of a succinic acid-producing recombinant S. cerevisiae hinted a metabolic engineering strategy involving expression of a malic acid transporter from Schizosaccharomyces pombe (MAE1) to export succinic acid out of cells [16].…”
Section: Production Of Bulk Chemicalsmentioning
confidence: 99%